Effects of protein and carbohydrate ingredients on colour of baked milk products - Mandiuk, Olena; Lohinova, Anna; Arsenieva, Larisa; Petrusha, Oksana; Polishchuk, Galyna (My University, 2024)
The aim of the present research was to study the influence of the presence of protein and carbohydrate ingredients on intensity of the Maillard reaction in baked dairy products and their color. Materials and methods. Cream with a fat content of 10%, as well as creams with the addition of whey protein, hydrolysed whey concentrates, and glucose-fructose syrup served as objects of study. The color characteristics of the baked milk cream were examined by the CIE Lab system using a digital colorimeter; the active acidity was determined by the potentiometric method, and the overall sensory quality was estimated by the weighted average of the scores.

Метою цього дослідження було вивчення впливу наявності білкових та вуглеводних інгредієнтів на інтенсивність реакції Майяра у випечених молочних виробах та їх колір. Об'єктами 10%, а також вершки з додаванням сироваткового білка, гідролізованих концентратів сироватки та глюкозно-фруктозного сиропу. Колірні характеристики випечених молочних вершків досліджували за допомогою системи CIE Lab з використанням цифрового колориметра; активну кислотність визначали потенціометричним методом, а загальну сенсорну якість оцінювали за середньозваженим значенням балів.
Keywords: baked milk; sour cream; milk protein concentrate; cooking cream; the color of baked milk; кафедра технології молока і молочних продуктів; кафедра експертизи харчових продуктів; колір пряженого молока; колір вершків; молочно-білковий концентрат; варіння вершків; реакція Майяра